Significant Role of the Human Development Index in Alleviating Poverty - Lestari, Etty Puji; Rahayu, Heffi Christya; Retnaningsih, Tri Kurniawati; Suhartono, Suhartono (Journal of Social Economics Research, 2022)
During the pandemic, most of the population not only experienced a decrease in income but also experienced losses in various dimensions of life, such as health, education, and a decent standard of living. So far, poverty is measured by expenditure, and it has not been able to capture all of the above dimensions. Assessing multidimensional poverty provides more specific information so that policies are more relevant. This study evaluates factors and policies related to poverty in Indonesia, especially during the pandemic, using pooled data regression. The variables used are the Human Development Index (HDI), gross domestic product (GDP), population, and wages in 34 provinces in Indonesia from 2012 to 2021. The results show that HDI has a significant negative influence and population has a positive and significant influence on poverty. In Indonesia, the pandemic reduced people’s incomes, which increased poverty. Unlike other studies, this study shows that the 2020 wage stagnation policy implemented by the government effectively reduces poverty in Indonesia. During this period of economic recovery, the policies for providing employment and meeting public needs are believed to reduce the level of poverty.